Self-acceptance among patients with heart failure - Rayhan Nur Hakim; Beti Kristinawati (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Heart failure is a clinical syndrome disease that is very vulnerable to death. This condition will affect the patient's self-acceptance. Patients with heart failure will find it challenging to go about their daily lives, often feeling anxious, tense, depressed, and unable to control their own emotions. Purpose : To identify self-acceptance among patients with heart failure. Method: A descriptive quantitative research design was used in this study involving a sample of 294 patients. The technique used to take samples uses purposive techniques. Researchers have set inclusion criteria in patients with NYHA functional class I-III. The study did not include patients with a history of congenital heart disease. The AIS (acceptance of illness) instrument consisting of 8 questions was used in the study to determine the patient's self-acceptance. Results: The study in heart failure patients showed that 77.9% of the 294 respondents showed high self-acceptance, while low self-acceptance amounted to 22.1%. Conclusion: The analysis's results suggest that most patients with heart failure have high self-acceptance.